Study on structural characteristics and physicochemical properties of starches extracted from three varieties of kudzu root (Pueraria lobata starch). Issue 3 (27th January 2023) - Duan, Xuantong; Guan, Yongmei; Dong, Huanhuan; Yang, Mei; Chen, Lihua; Zhang, Hua; Naeem, Abid; Zhu, Weifeng
Abstract: Kudzu root ( Pueraria lobata ) is well known for its traditional use as a medicinal food homologous plant in China. Three varieties of kudzu roots, such as Gange‐1, Gange‐2, and Gange‐6, are commonly used. Nowadays, kudzu starch (KS) is commercially available as satiating foods or product ingredients. Differentiation and selection of the variety are important components of quality control for KS‐based products. Thus, the present work was aimed at comparing the physicochemical properties, such as thermodynamic properties, pasting properties, solubility, swelling, as well as the structural characteristics of the starches extracted from the three varieties of kudzu roots. The results show that KS‐6 has a higher content of functional ingredients thus can be used as an ideal functional starch. However, KS‐6 has a higher amylopectin:amylose ratio of 4.65, resulting in a better solubility, higher transition temperature, and higher gelatinization enthalpy. KS‐2 showed lower transition temperature and gelatinization enthalpy, as well as higher peak viscosity, through viscosity, and final viscosity. KS‐1 could result in a soft texture after pasting. The appropriate variety of KS should be differentiated and selected according to application scenarios. This study provided valuable insights into the potential use of different KS in the food and nonfood industries. Practical Application: 1. KS‐1 was found to be suitable for use as a food supplement. 2. KS‐6 has the highest nutritional value. 3. They can be used as a substitute for other similar starches.